2022
DOI: 10.3390/jimaging8060174
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Reconstruction of Images from Patterns Generated by Deterministic or Random Optical Masks—Concepts and Review of Research

Abstract: Indirect-imaging methods involve at least two steps, namely optical recording and computational reconstruction. The optical-recording process uses an optical modulator that transforms the light from the object into a typical intensity distribution. This distribution is numerically processed to reconstruct the object’s image corresponding to different spatial and spectral dimensions. There have been numerous optical-modulation functions and reconstruction methods developed in the past few years for different ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…From the manufacturing side, it is necessary to fabricate multilevel structures to improve the efficiency from the current 40% to >90%, which increases the cost and time of fabrication. With the latest developments in Femtosecond fabrication methods, it is possible to rapidly manufacture high-efficiency diffractive optical elements at a low cost [77][78][79]. The second challenge lies in the current performances of computational reconstruction methods.…”
Section: Discussionmentioning
confidence: 99%
“…From the manufacturing side, it is necessary to fabricate multilevel structures to improve the efficiency from the current 40% to >90%, which increases the cost and time of fabrication. With the latest developments in Femtosecond fabrication methods, it is possible to rapidly manufacture high-efficiency diffractive optical elements at a low cost [77][78][79]. The second challenge lies in the current performances of computational reconstruction methods.…”
Section: Discussionmentioning
confidence: 99%
“…, where α and β are real numbers searched until the lowest reconstruction noise quantified by the entropy is obtained, arg(•) refers to the phase, and I is the Fourier transform of I. It has been recently observed that NLR applied to different types of deterministic optical fields generated a reconstruction spot close to the diffraction-limited spot 37 .…”
Section: Methodsmentioning
confidence: 99%
“…, where  and  were tuned between -1 to 1 until a minimum entropy is obtained [12]. Even though NLR has a wide applicability range involving different optical modulators, the resolution is limited by the autocorrelation function 𝑃𝑆𝐹 * 𝑃𝑆𝐹 [13]. This imposes a constraint on the nature of PSF and, therefore on the type of aberrations that can be corrected.…”
Section: Methodsmentioning
confidence: 99%